MAFLD Criteria May Overlook a Subtype of Patient with Steatohepatitis and Significant Fibrosis - Huang J (Dove Medical Press, 2021)
Jiaofeng Huang,1,* Wenjuan Xue,2,* Mingfang Wang,1 Yinlian Wu,1 Medha Singh,3 Yueyong Zhu,1,4 Rahul Kumar,5 Su Lin1 1Department of Hepatology, Hepatology Research Institute, The First Affiliated Hospital, Fujian Medical University, Fuzhou, Fujian, 350005, People’s Republic of China; 2Department of Traditional Chinese Medicine, The First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350005, People’s Republic of China; 3Department of General Medicine, Tan Tock Seng Hospital, Singapore; 4Fujian Key Laboratory of Precison Medicine for Cancer, the First Affiliated Hospital, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 5Department of Gastroenterology and Hepatology, Duke-NUS Academic Medical Centre, Changi General Hospital, Singapore*These authors contributed equally to this workCorrespondence: Su LinDepartment of Hepatology, Hepatology Research Institute, The First Affiliated Hospital, Fujian Medical University, No. 20, Chazhong Road, Taijiang District, Fuzhou, Fujian, 350005, People’s Republic of ChinaTel +86 591-87981657Fax +86 591-87982526Email sumer5129@fjmu.edu.cnIntroduction: Metabolic associated fatty liver disease (MAFLD) is a novel concept for fatty liver disease. Different from non-alcoholic fatty liver disease (NAFLD), the diagnosis of MAFLD requires the presence of metabolic risks. This study aimed to characterize patients with liver steatosis but without metabolic risks (non-MR-steatosis) which may not be diagnosed by MAFLD criteria.Methods: Consecutive patients who underwent biopsy were included in this study. The clinic-pathological characteristics of non-MR-steatosis, NAFLD and MAFLD were compared.Results: A total of 1217 cases were included. There were 426 (35.00%) cases with MAFLD, 585 (48.07%) with NAFLD and 168 (13.80%) with non-MR-steatosis. The majority of the cases were infected with HBV (93.26%). The age and metabolic profiles were highest in MAFLD and lowest in non-MR-steatosis. The body mass index (BMI) level was also lowest in non-MR-steatosis (20.78 ± 1.54 kg/m2). The ALT and AST levels of the non-MR-steatosis group were not statistically different from those of MAFLD or NAFLD groups (p > 0.05). Histologically, there was no significant difference in the degrees of inflammation and fibrosis among the three groups. The severity of steatosis in non-MR-steatosis group was lower than MAFLD or NAFLD groups (p < 0.05). These results were consistent in both HBV and non-HBV subgroups.Conclusion: MAFLD criteria may overlook some steatotic patients without metabolic risks, who may also have steatohepatitis and significant fibrosis.Keywords: metabolic associated fatty liver disease, nonalcoholic fatty liver disease, metabolic risks, lean NAFLD, biopsy